2013
DOI: 10.1159/000348494
|View full text |Cite
|
Sign up to set email alerts
|

Rectal Villous Adenoma with McKittrick-Wheelock Syndrome: Report of a Rare Case

Abstract: Background: McKittrick-Wheelock syndrome mostly results from colorectal villous adenoma and is characterized by dehydration, hyponatremia, hypokalemia, and prerenal azotemia. Case Report: We report the case of an 84-year-old patient with rectal villous adenoma, presenting with chronic mucous diarrhea for 2 years and subsequent prerenal azotemia. After fluid and electrolyte replenishment, the patient underwent proctectomy and recovered completely. Conclusion: According to a review of the literature, we suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Nevertheless, the numbers are very small, and previous papers have suggested that pharmacological treatments add no benefit beyond appropriate fluid and electrolyte replacement. 20 Based our findings, medical management would definitely be worth considering if a patient is not fit for surgery or chooses not to undergo surgical intervention.…”
Section: Medical Managementmentioning
confidence: 80%
“…Nevertheless, the numbers are very small, and previous papers have suggested that pharmacological treatments add no benefit beyond appropriate fluid and electrolyte replacement. 20 Based our findings, medical management would definitely be worth considering if a patient is not fit for surgery or chooses not to undergo surgical intervention.…”
Section: Medical Managementmentioning
confidence: 80%
“…Rectal effluent in a case report demonstrated levels 3 to 6 times higher of PGE2 from a villous adenoma [ 9 ]. Hypersecretion can also result in severe azotemia along with electrolyte imbalances that could lead to cardiac arrhythmias and, in severe cases, rhabdomyolysis or altered mental status may be seen [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…The larger and more distal the adenoma, the more severe the syndrome. The hypersecretion may be so severe that severe azotemia may result [4].…”
Section: To the Editormentioning
confidence: 99%